Family educational care of the blind children and its relationship to their social adaptation - Imam, Abdelrahman Gibreel (Journal of Educational and Psychological Sciences, 2025)
This thesis handles the role played by the family educational care in achieving the social adaptation of the blind children and to know the level of educational care for the family's upon them. The study adopts the descriptive methodology to shed light on this problem through description and close understanding of its present circumstances. Following are the tools used for the study: 1- Vineland Social Maturity Measurement (as amended by the researcher). 2- Blind Children Households Questionnaire (prepared by the researcher). The study sample is composed of (100) blind children of Alnour school for the Education and Promotion of blind children of which (78) male and (22) female upon whom the measurement is applied and that the household questionnaire is conducted upon their families. The study comes out with the following findings: 1-The level of the family educational care provided by the families to blind children can be described as above medium. 2-There is a direct correlation of statistical significance (R=0,252) between the degrees of the family educational care methods and the degrees of social adaptation of the blind children. 3-There is a reverse correlation (R=0,775) between the age and the degrees of social adaptation of the blind children. 4-There are no differences of statistical significance in the degree of social adaptation between the blind children that can be attributed to the sex (male and female) or the degree of blindness (completely – partially). The most important recommendations of the study are the necessity of accepting the blind children by family's, train them for social interaction and self-reliance, develop their perceptions and indoctrinate them good conduct so as to guarantee their social adaptation.
Keywords: Family educational care; blind children; social adaptation